Generality In Socio-Philosophical Heritage - Otabek Ortikov (Peerian Journals Publishing, 2023)
Universal values are considered a set of characteristics and norms of a person's coexistence, positive and justified qualities at a certain time. They are often considered innate to human nature. Universal values are the subject of the study of ethics, ethics and philosophy. In particular, Axiology devotes its research to values and evaluation conclusions, and human rights are based on what is considered universal values. This article analyzes universal values from the point of view of socio-philosophical heritage.
Keywords: heritage; human nature; human rights